On fixed and coincidence points under contractive mappings in non-archimedean fuzzy metric space - Panwar, Anju (International Journal of Applied Mathematical Research, 2012)
In this paper, we prove some coincidence and fixed point theorems for various contractive mappings in spherically complete non-archimedean fuzzy metric space. In this space, we also prove the metric locally constancy of a function f. Our results extend various known results in ultra metric space.